Transformasi Digital dalam Administrasi Publik: Studi Komparatif di Indonesia dan Korea Selatan - Erinaldi, Erinaldi; Angelina Ramadhani; Murni Murni; Mutia Rahmah Sari; Ulfa Muti’ah (Studi Administrasi Publik dan ilmu Komunikasi, 2026)
Digital transformation in public administration has become one of the strategic agendas in modern bureaucratic reform to improve the effectiveness, efficiency, transparency, and quality of public services. This study aims to analyze the digital transformation of public administration through a comparative study between Indonesia and South Korea, particularly in the implementation of digital government. This study uses a qualitative method with a comparative study approach and is supported by library research through secondary data collection from scientific journals, international agency reports, government policy documents, and relevant previous research. The data analysis technique uses descriptive-comparative analysis with the theoretical approaches of Digital Era Governance (DEG), Institutional Theory, New Public Management (NPM), and Socio-Technical Systems Theory. The results of the study show that South Korea has succeeded in developing an integrated digital government because it is supported by consistent national policies, strong data interoperability, high bureaucratic capacity, adaptive organizational culture, and equitable distribution of digital infrastructure. In contrast, Indonesia is still in the transition stage from e-government to digital government and faces various obstacles such as fragmentation of inter-agency systems, low data interoperability, inequality in digital infrastructure, limited ASN competency, and bureaucratic resistance to change. Based on the Digital Era Governance theory, South Korea has successfully implemented the principles of reintegration, needs-based holism, and digitization of changes, while Indonesia remains suboptimal in terms of bureaucratic integration and services based on public needs. This study concludes that the success of digital transformation in public administration is determined more by institutional strength and bureaucratic reform than simply by technology adoption. Therefore, Indonesia needs to prioritize digital transformation as a comprehensive national reform agenda to create a modern, responsive, and service-oriented government.